The influence of geomagnetic and seismic parameters on mortality from cardiovascular pathologies in the Shamakhi Region of the Republic of Azerbaijan - L. G. Afandieva (Евразийский Кардиологический Журнал)
Aim. Study of the dependence of mortality from CVD on helio-seismic indicators in the Shamakhi region of the Republic of Azerbaijan.Materials and methods. 352 case histories of patients who died in 2013 from various diseases were reviewed. The relationship was established between the number of deaths, their causes, distribution by sex and age with the magnitude of earthquakes, the depth of the epicenter and seismological activity by months. The data obtained were statistically processed using the Statistica 12.0 for Windows software package (Statsoft Inc., USA). To establish correlations, Pearson Chi-Square Tests was calculated, the results were considered reliable at p <0.05.Results. Statistically significant (p <0.001) more deaths were observed at the age of 80-89 years in men, and at the age of 70-79 years in women. Also, the relationship between mortality and the depth of the seismic process and the magnitude of the earthquake was established, in particular, the greatest number of deaths was observed at a depth of the seismic process <10 km and with a magnitude of 1.1-2.0 ml. In all months, the number of deaths was higher with a magnitude of 1.1-2.0 Ml. Statistically significant (p <0.005) was the fact that the nosology of the studied diseases was dependent on the age of the patients. Thus, a greater number of deaths in all age groups accounted for heart failure. A statistically significant (p <0.005) dependence of the depth of the seismic process on the month of death of patients was established, in particular, for all months, deaths coincided with the depth of the process less than 10 km. At the age of 40-70 years, a significantly greater number of deaths were from heart failure in men, and from 70 years and above in women.Conclusion. Thus, there is a close correlation between geomagnetic changes and mortality from CVD, which is realized in the form of an increase in the frequency of cases and deaths, and the number of these cases increases with the age of patients and changes in the magnitude and depth of the earthquake.